Inoculation of tomato plants with rhizobacteria enhances the performance of the phloem-feeding insect Bemisia tabaci - Shavit, Roee; Ofek-Lalzar, Maya; Burdman, Saul; Morin, Shai (Frontiers in Plant Science, 2013)
In their natural environment, plants experience multiple biotic interactions and respond to this complexity in an integrated manner. Therefore, plant responses to herbivory are flexible and depend on the context and complexity in which they occur. For example, plant growth promoting rizhobacteria (PGPR) can enhance plant growth and induce resistance against microbial pathogens and herbivorous insects by a phenomenon termed induced systemic resistance (ISR). In the present study, we investigated the effect of tomato (Solanum lycopersicum) pre-inoculation with the PGPR Pseudomonas fluorescens WCS417r, on the performance of the generalist phloem-feeding insect Bemisia tabaci. Based on the ability of P. fluorescens WCS417r to prime for ISR against generalists chewing insects and necrotrophic pathogens, we hypothesized that pre-inoculated plants will strongly resist B. tabaci infestation. In contrast, we discovered that the pre-inoculation treatment increased the tomato plant suitability for B. tabaci which was emphasized both by faster developmental rate and higher survivability of nymph stages on pre-inoculated plants. Our molecular and chemical analyses suggested that the phenomenon is likely to be related to: (I) the ability of the bacteria to reduce the activity of the plant induced defense systems; (II) a possible manipulation by P. fluorescens of the plant quality (in terms of suitability for B. tabaci) through an indirect effect on the rhizosphere bacterial community. The contribution of our study to the pattern proposed for other belowground rhizobacteria and mycorrhizal fungi and aboveground generalist phloem-feeders is discussed.